THE EFFECT OF THE STUDENT TEAM ACHIEVEMENT DIVISION (STAD) METHOD ON THE ACTIVITY AND LEARNING OUTCOMES OF MENU DESIGN IN VOCATIONAL HIGH SCHOOLS - Febriana, Rina; Farihah, Nuraina; Rusilanti, Rusilanti (Jurnal Pendidikan Teknik dan Vokasional, 2023)
The purpose of this research is to study the influence of the STAD method toward dynamic behavior and learning outcomes of the student in the Designing Menu subject of Restaurant and F&B Service at Grade XI Culinary Class in SMK Negeri 3 Bogor odd semester year 2019/2020. This research using a purposive sampling technique, so that are two classes of XI Culinary, in which every level has 34 students. Assessing the influence of the STAD method toward dynamic behavior is done by two times of activity observed at the experimental class. The first observation does the teacher center learning, and the second observation does the STAD. Assessing the influence of STAD method toward learning outcome is done by doing an empirical validation, and doing pre-test and post-test at the control class and the experimental level. This research calculates the actual behavior with descriptive analysis and for the learning outcome using pre and post-test. Based on the Mann Whitney U test on student learning outcomes show there is a positive influence on student learning outcomes. There is an influence of the STAD method on the activeness and learning outcomes of students in SMK on the subject of Menu Design. With an increase in the average value of activeness of 16.2% and the average cost of student learning outcomes by 17.47, which is higher than the learning outcomes of students who use the lecture method. These results indicate that the application of the STAD method had applied to other theoretical subjects in the Subjects of Food and Beverage Administration.